2005
DOI: 10.1177/147323000503300410
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Peripheral Neuropathy Using Measurement of the Current Perception Threshold with the Neurometer® in Patients with Type 2 Diabetes Mellitus

Abstract: Measurement of current perception threshold (CPT) using the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 29 publications
2
48
1
1
Order By: Relevance
“…The pulses at 2,000, 250, and 5 Hz mainly stimulate large myelinated (A␤-), small myelinated (A␦-), and small unmyelinated (C-) fibers, respectively. The neurometer is now widely used clinically to evaluate the effects of analgesic drugs and peripheral nerve function in various painful neuropathies, including DPN (45)(46)(47)(48). Although previous studies (15,49 -51) reported methods for measurement of the current perception threshold with the neurometer in rats and sensory nerve functions in animals, no studies have evaluated STZ-induced diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The pulses at 2,000, 250, and 5 Hz mainly stimulate large myelinated (A␤-), small myelinated (A␦-), and small unmyelinated (C-) fibers, respectively. The neurometer is now widely used clinically to evaluate the effects of analgesic drugs and peripheral nerve function in various painful neuropathies, including DPN (45)(46)(47)(48). Although previous studies (15,49 -51) reported methods for measurement of the current perception threshold with the neurometer in rats and sensory nerve functions in animals, no studies have evaluated STZ-induced diabetic animals.…”
Section: Discussionmentioning
confidence: 99%
“…The CPT evaluation was performed at the 3 frequencies, 2000 Hz, 250 Hz and 5 Hz, corresponding to evaluation of the Aβ, Aδ and C fibers 7,8) . In theory, the effect of TENS on each of these 3 types of fibers should be different since they represent three different neurophysiological mechanisms of pain 2) .…”
Section: Discussionmentioning
confidence: 99%
“…A commonly used CPT device is the Neurometer NS3000 (Neurotron Inc., Baltimore, Maryland, USA) which employs a constant alternating sinusoidal current to deliver electrical stimulus at frequencies of 2000, 250 and 5 Hz 7) . It has been reported that these 3 frequencies can selectively stimulate, and therefore assess, the large myelinated Aβ fibers, the small myelinated Aδ fibers, and the unmyelinated C fibers, respectively 7,8) . Since CPT devices are usually constant current stimulators, skin impedance is not a limiting factor and the results are unaffected by skin temperature, skin thickness or elasticity 9) .…”
Section: Introductionmentioning
confidence: 99%
“…The Neurometer Ò (Neurotron, Inc., Baltimore, MD, USA) is an example of such a device; it has been used clinically to detect peripheral neuropathy in diabetic individuals. [1][2][3][4][5][6][7] By measuring CPT and CPT trends, transcutaneous nerve stimulation has been suggested as an effective tool in diagnosing and monitoring conditions associated with worsening peripheral neuropathy (i.e., increasing CPT values), such as diabetes mellitus or vibration-induced neuropathy. 2 Current standard techniques for determining nerve block effectiveness are limited by the inherent subjectivity of patient self-reporting (e.g., cold test, pinprick tests).…”
Section: Résumémentioning
confidence: 99%